MPO-ANCA-Associated Hypertrophic Pachymeningitis Mimicking IgG4-Related Disease: A Case Report and Literature Review - Chen Y; Liu L; Xie C (Journal of Inflammation Research, 2025)
Yuxue Chen,1 Lu Liu,2 Cuihong Xie3 1Department of Rheumatology and Immunology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People’s Republic of China; 2Department of Pharmacy, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People’s Republic of China; 3Department of Emergency and Critical Care Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People’s Republic of ChinaCorrespondence: Cuihong Xie, Department of Emergency and Critical Care Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, 1095th Jiefang Avenue, Wuhan, 430030, People’s Republic of China, Tel +86-13628699465, Fax +86-27-83665264, Email jiecuihong@tjh.tjmu.edu.cnAbstract: Hypertrophic pachymeningitis (HP) is a rare and chronic clinical disease characterized by thickening of the dura mater, leading to persistent headache, cranial neuropathy, seizures, and other neurological symptoms. Immune-mediated causes, particularly antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis and IgG4-related disease (IgG4-RD), are among the most common etiologies. We report a case of a 54-year-old female with recurrent headache, blepharoptosis, hearing loss, and markedly elevated inflammatory markers. Blood tests, and serum levels of IgG4 were within normal ranges. Contrast enhanced cranial MRI revealed thickening and enhancement of bilateral cerebral hemispheres and tentorial dural maters. Additional findings included mild left lacrimal gland enlargement, bilateral middle ear mastoiditis, and tympanic tegmen destruction. Abdominal high-resolution computed tomography (CT) showed enlarged retroperitoneal lymph nodes. Histopathology demonstrated dense lymphoplasmacytic and neutrophilic infiltration with 80 IgG4-positive plasma cells per high-power field and an IgG4+/IgG+ cell ratio of 20%. An initial diagnosis of possible IgG4-RD was made. However, the patient’s symptoms responded poorly to prednisolone (20 mg/day), and fever ensued. Pseudomonas aeruginosa, nocardia malleis, and leptocyclus virus were found in the cerebrospinal fluid measured by NGS. Subsequent laboratory testing showed positive p-ANCA and anti-myeloperoxidase antibodies (anti-MPO), with a negative anti-nuclear antibodies panel, leading to a revised diagnosis of MPO-ANCA-associated HP. Treatment was escalated to intravenous methylprednisolone (40 mg/day), cyclophosphamide, and anti-infectious agents, leading to improved symptoms and decreased inflammatory markers. However, there was a recurrence during the taper of prednisolone. The addition of rituximab achieved complete remission. MPO-ANCA-associated HP is a rare inflammatory disorder that brings diagnostic challenges and requires comprehensive differential diagnosis. In relapsed or refractory cases, rituximab may be a valuable therapeutical option.Keywords: IgG4-related disease, hypertrophic pachymeningitis, ANCA-associated vasculitis, rituximab